Formation de professionnels pluri-catégoriels en matière de compétences psychosociales : perspectives andragogiques, professionnalisation et développement professionnel - Philippe Cury; Carine Simar (Nantes Université, 2023)
This article analyzes the tensions between professionalization and professional development of multi-category professionals working with young people aged 7 to 12 engaged in an adult training system in psychosocial skills (CPS). The CPS are one of the emblematic objects in order to develop the promotion of the health and well-being of children. This article aims to question the relevance of the deployment of adult training in order to professionalize CPS and if this is the case, what would be its characteristics and for what effects? The theoretical framework is based on the analysis of the activity with reference to ergonomic psychology and calls upon three other notions: andragogy, professionalization and professional development. A qualitative methodology based on the conduct of semi-structured interviews (30) with multi-category professionals involved in this system was implemented. Professional development indices have been identified according to the andragogical and professionalization characteristics of the training deployed.